Diversity and Conservation of Carnivores in Saudi Arabia - Ali Al Ahmari; Farah Neyaz; Faisal Shuraim; Abdul Rahman Al Ghamdi; Ahmad Al Boug; Mesfer Alhlafi; Sharif Al Jbour; Francesco M. Angelici; Saleh Alaamri; Khalid Al Masabi; Zuhair Sami Amr (Diversity)
In the present study, we updated the taxonomy and distributional data for 14 carnivore species based on previous records and the recent results of camera trapping (4787 camera nights from 58 locations) and depicted species richness. We then identified threats and the conservation measures that are practiced to ensure the protection of the carnivores of Saudi Arabia. A total of 10 species of carnivores (Canis aureus, Canis lupus, Caracal caracal, Felis lybica, Genetta genetta, Hyaena hyaena, Ichneumia albicauda, Mellivora capensis, Vulpes cana, and Vulpes vulpes) were recorded based on camera trapping efforts. The striped hyena was the most recorded species in 13 locations, with the highest number of observations made at Raydah Protected Area, followed by the red fox and the Arabian wolf. Both Genetta genetta and Mellivora capensis were the least recorded species. Vulpes vulpes was the most distributed species and it was recorded from 15 sites. The southwestern corner of Saudi Arabia covering the Asir, Jazan, and Najran Plateaus extending further into the Al Sarawat Mountains hosts the highest number of carnivore species. Major threats affecting carnivores include killing and animal trade. The status of the critically endangered species, Panthera pardus nimr, was discussed. Threats and the conservation status based on regional assessment according to the IUCN Red List of the carnivores of Saudi Arabia were documented and highlighted.